Regulation of orthopaedic devices: Future implications for research and innovation - Claire A. Donnelley, BS; Vincent J. Devlin, MD; Mitchel B. Harris, MD, FACS; Robert A. Poggie, PhD; Roy W. Sanders, MD; Saam Morshed, MD, MPH, PhD (OTA International, 2021)
Abstract. The conception-to-market development of orthopaedic devices occurs across the total product life cycle including device design and preclinical testing, clinical investigations to support marketing applications, and monitoring of device performance after market introduction. This process involves industry, regulatory agencies, health care providers, engineers, scientists, and patients. The Food and Drug Administration (FDA) is responsible for regulating medical devices in the United States, and uses a 3-tier classification system based on the level of control necessary to provide reasonable assurance of safety and effectiveness. Classification directs the required regulatory pathway and premarket submission type. Variations in global regulations, particularly between the United States, European Economic Area (EEA), and the United Kingdom (UK), may impact industry response to orthopaedic device development. Changing device innovation and reimbursement models have led to the consolidation of market share among larger companies. Although larger companies are better able to cope with more rigorous regulatory requirements, this leads to decreased competition and increased upward price pressure. To assist with the complex regulatory processes, the FDA offers pre-submission assistance as an opportunity for early collaboration and discussion about the medical device or device-led combination product submissions. Orthopaedic organizations, such as the Orthopaedic Trauma Association (OTA), may assist in postmarket device surveillance through the coordinated development and maintenance of clinical data registries. Such registries can longitudinally follow patients with a specific orthopaedic pathology or device usage, and monitor outcomes towards improvements in next-generation device development. As technology evolves, the nexus of regulation, industry, and patient outcome monitoring will continue to support safe and effective device innovation.